Comparison Between Minimally Invasive Surgery and Conventional Open Surgery for Patients With Spinal Metastasis: A Prospective Propensity Score-Matched Study. Issue 10 (15th May 2017) - Hansen-Algenstaedt, Nils; Kwan, Mun Keong; Algenstaedt, Petra; Chiu, Chee Kidd; Viezens, Lennart; Chan, Teik Seng; Lee, Chee Kean; Wellbrock, Jasmin; Chan, Chris Yin Wei; Schaefer, Christian
Abstract : Study Design: Prospective propensity score-matched study. Objective: To compare the outcomes of minimal invasive surgery (MIS) and conventional open surgery for spinal metastasis patients. Summary of Background Data: There is lack of knowledge on whether MIS is comparable to conventional open surgery in treating spinal metastasis. Methods: Patients with spinal metastasis requiring surgery from January 2008 to December 2010 in two spine centers were recruited. The demographic, preoperative, operative, perioperative and postoperative data were collected and analyzed. Thirty MIS patients were matched with 30 open surgery patients using propensity score matching technique with a match tolerance of 0.02 based on the covariate age, tumor type, Tokuhashi score, and Tomita score. Results: Both groups had significant improvements in Eastern Cooperative Oncology Group (ECOG), Karnofsky scores, visual analogue scale (VAS) for pain and neurological status postoperatively. However, the difference comparing the MIS and open surgery group was not statistically significant. MIS group had significantly longer instrumented segments (5.5 ± 3.1) compared with open group (3.8 ± 1.7). Open group had significantly longer decompressed segment (1.8 ± 0.8) than MIS group (1.0 ± 1.0). Open group had significantly more blood loss (2062.1 ± 1148.0 mL) compared with MIS group (1156.0 ± 572.3 mL). More patients in the open group (76.7%) needed blood transfusions (with higher average units of blood transfused) compared with MIS group (40.0%). Fluoroscopy time was significantly longer in MIS group (116.1 ± 63.3 s) compared with open group (69.9 ± 42.6 s). Open group required longer hospitalization (21.1 ± 10.8 days) compared with MIS group (11.0 ± 5.0 days). Conclusion: This study demonstrated that MIS resulted in comparable outcome to open surgery for patients with spinal metastasis but has the advantage of less blood loss, blood transfusions, and shorter hospital stay. Level of Evidence: 3